2022
DOI: 10.2196/34605
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Implementation of Digital Innovations in Response to the COVID-19 Pandemic to Address Key Public Health Functions: Scoping Review of Academic and Nonacademic Literature

Abstract: Background Digital technologies have been central to efforts to respond to the COVID-19 pandemic. In this context, a range of literature has reported on developments regarding the implementation of new digital technologies for COVID-19–related surveillance, prevention, and control. Objective In this study, scoping reviews of academic and nonacademic literature were undertaken to obtain an overview of the evidence regarding digital innovations implemente… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Commonly used digital data sources include social media and aggregate search query data, where initial surveillance applications date from the early 2000s, as well as participatory surveillance methods, such as repeated cross-sectional online surveys and crowdsourcing of photos or sample submissions (( 9 )). More recently, PHS applications of other digital technologies are being explored, such as mobility data and the Internet of Things (IoT), which includes wearable devices and other physical objects that connect and exchange data via the Internet (( 8 )). Digital data sources may have the potential to provide more timely information and capture populations that may not seek health care; although possible to use as an independent source of information, they are generally considered to be complementary to traditional surveillance data (( 9 )).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Commonly used digital data sources include social media and aggregate search query data, where initial surveillance applications date from the early 2000s, as well as participatory surveillance methods, such as repeated cross-sectional online surveys and crowdsourcing of photos or sample submissions (( 9 )). More recently, PHS applications of other digital technologies are being explored, such as mobility data and the Internet of Things (IoT), which includes wearable devices and other physical objects that connect and exchange data via the Internet (( 8 )). Digital data sources may have the potential to provide more timely information and capture populations that may not seek health care; although possible to use as an independent source of information, they are generally considered to be complementary to traditional surveillance data (( 9 )).…”
Section: Resultsmentioning
confidence: 99%
“…Many of these data sources and AI methods were used during the coronavirus disease 2019 (COVID-19) pandemic, where timely and complete information was crucial to understanding and responding to evolving pandemic risks ( 4 ). The rapid development of these innovative surveillance methods and use of novel data sources suggests the need to take a closer look at the scientific maturity, as well as the feasibility and utility of their use, in real-world applications (( 5 , 6 , 8 )). The objective of this paper is to highlight examples of the application of innovative methods to PHS and provide insights for public health authorities on the potential benefits, risks, and challenges of using non-traditional data sources and methods in PHS.…”
Section: Introductionmentioning
confidence: 99%
“…In light of the ramifications associated with digital public health surveillance, the value of these forms of surveillance must be carefully weighed. Recent publications have suggested that the wide range of digital technologies implemented during the COVID-19 pandemic for surveillance purposes faced a number of barriers preventing their successful implementation, and while many of these digital innovations have yet to be formally evaluated or assessed, there is significant uncertainty around their value [ 8 , 9 ]. It is difficult to determine the impact of digital surveillance on disease transmission, particularly given the challenges around technology uptake, implementation, and consistency.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the extensive use of a plethora of digital solutions for public health surveillance, their actual efficacy in predicting disease spread or supporting public health responses has been unclear [ 8 , 9 ], and there remain ongoing questions about the ethical dimensions of digital surveillance. For instance, the use of digital tools by the state, its agents, the private sector, and other actors has raised concerns around the potential consequences of surveillance, particularly for those who are most marginalized [ 10 - 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has highlighted health inequalities, especially in low-income countries [2,3]. The need for social isolation relied on the creativity of the care teams and managers of health facilities to quickly transpose face-to-face practices to remote ones [4].…”
mentioning
confidence: 99%